Monstrous Reading: The Martyrology After de Man - Clark, David L. (Studies in Canadian Literature, 1990)
As readers approach bp Nichol's long poem The Martyrology, they commence by reading (of) Nichol's death, itself utterly senseless and unrepresentable and yet fully inscribed in a poem whose final form is what it is exactly because of it. Yet, Nichol's death, like the materiality of the letter, constitutes the most fundamental point of resistance to the poem's reading; that is, according to Paul de Man's theory that language is ultimately not human, Nichol's death -- its unthinkability, its refusal to be understood -- disfigures The Martyrology, defacing or marking the text precisely by unmasking its readability as a humane figure imposed upon a monstrously indifferent otherness. Moreover, as one continues to read the poem and examine its inhuman language, one can see a connection between Saussure's understanding of how signifying systems in language operate and the exorbitant treatment of language in Nichol's work (especially in Book 5), for, by dismembering words into letters, Nichol brings out the relationship between meaningfulness and the literal, material properties of language.